(untitled) (Journal of Mechanical Engineering, 2011)
This paper presents mechanical properties of A356 matrix nanocomposites fabricated by reinforcing nano silicon carbide (SiC) particles at 0.1 to 0.5 weight percent with the aid of ultrasonic cavitation. SiC nanoparticles synthesized by bottom-up and top-down approach are used in this work as reinforcements and change in mechanical properties are observed. For comparision, A356 matrix composite reinforced with microparticles at 0.5 wt% by stir casting also prepared. Till now, SiC nanoparticles produced by bottom up approach were used as reinforcements in A356 alloy by so many researchers to improve mechanical properties. But in this work, nanoparticles produced by high energy ball milling (Top-down approach) are also used as reinforcements. It is observed that there is reduction in tensile properties for the composites prepared using nanoparticles via top down approach than that of bottom up approach. But significant increase compared to the composites prepared by reinforcing same amount of microparticles by stir casting. The reasons may be due to the non-uniformity in size of particles and contamination while milling nanoparticles. However, the change in properties is less and use of nanoparticles via top down approach is admissible when compared to the cost of nanoparticles synthesized from bottom up approach or chemical routes. DOI: http://dx.doi.org/10.3329/jme.v41i2.7507